2015
DOI: 10.5565/rev/jtl3.597
|View full text |Cite
|
Sign up to set email alerts
|

Potential Inclusion of Multiple Intelligences in Jordanian EFL Textbooks: A Content Analysis

Abstract: This study examines the potential incorporation of the principles of the Multiple Intelligences Theory in the Jordanian Action Pack textbook for the first-, fourth-, eighth-and eleventh-grades by means of content analysis. The findings reveal that unlike the moral, existential and spiritual intelligences, which are not incorporated at all, the verbal/linguistic, intrapersonal and spatial/visual intelligences are better represented than other intelligences in the activities of the textbook. The findings further… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 24 publications
3
8
0
Order By: Relevance
“…Specifically, students who are in grade 9, 10 and 12 are given activities which pave the way for them to build linguistic knowledge rapidly. These findings are consistent with the findings of other studies (Al-Shboul and Al-Khawaldeh, 2014;Al-Omari et al, 2015) which revealed in their findings that verbal/linguistic intelligence is represented in a high manner in the analysed activities.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…Specifically, students who are in grade 9, 10 and 12 are given activities which pave the way for them to build linguistic knowledge rapidly. These findings are consistent with the findings of other studies (Al-Shboul and Al-Khawaldeh, 2014;Al-Omari et al, 2015) which revealed in their findings that verbal/linguistic intelligence is represented in a high manner in the analysed activities.…”
Section: Resultssupporting
confidence: 93%
“…The study of Al-Shboul and Al-Khawaldeh (2014) investigated the textbooks for grades 11 and 12. The study of Al-Omari et al (2015) analyzed the textbooks for grade 1, 4, 8, and 11. Different school textbook subject was analyzed, such as the study (Aboad, 2016) who examined a chemistry textbook.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(e.g. Ababneh, 2007;Al-Ghazo & Smadi;Al Habahabeh, 2016;Al Omari, Bataineh, & Smadi, 2015;Al Omari &Smadi, 2002;Karsou, 2005;Manasrah, Al-Sobh, & AL-Jabali, 2013;Zawahreh 2012. However, there is a scarcity of studies which analyzed ILOs and the learning activities in Action Pack Textbooks in light of the newly-developed EFL curriculum (Delete "objectives") in Jordan.…”
Section: Problem and Significance Of The Studymentioning
confidence: 99%
“…The researcher recommended that the activities in Action Pack (1-6) be reviewed in light of the General and Specific Learning Outcomes of the EFL Curriculum in Jordan. Al Omari et al (2015) investigated the principles of Multiple Intelligences Theory (MIT) which are incorporated in Action Pack textbooks in Jordan (grades 1, 4, 8, and 11) by means of content analysis. The findings revealed that the moral, existential and spiritual intelligences were not incorporated in the activities of the textbooks under study, and that the distribution of other intelligences was imbalanced in the textbooks.…”
Section: Previous Researchmentioning
confidence: 99%